Poly(I:C) Challenge Alters Brain Expression of Oligodendroglia-Related Genes of Adult Progeny in a Mouse Model of Maternal Immune Activation - Zhang, Xiao-Fan; Chen, Ting; Yan, Aifen; Xiao, Jia; Xie, Yong-Li; Yuan, Jing; Chen, Pin; Wong, Anderson On-Lam; Zhang, Yang; Wong, Nai-Kei (Frontiers in Molecular Neuroscience, 2020)
Background: Altered white matter connectivity, as evidenced by pervasive microstructural changes in myelination and axonal integrity in neuroimaging studies, has been implicated in the development of autism spectrum disorder (ASD) and related neurodevelopmental conditions such as schizophrenia. Despite an increasing appreciation that such white matter disconnectivity is linked to social behavior deficits, virtually no etiologically meaningful myelin-related genes have been identified in oligodendrocytes, the key myelinating cells in the CNS, to furnish an account on the causes. The impact of neurodevelopmental perturbations during pregnancy such as maternal immune activation (MIA) on these genes in memory-related neural networks has not been experimentally scrutinized. Methods: In this study, a mouse model of MIA by the viral dsRNA analogue poly(I:C) was employed to mimic the effects of inflammation during pregnancy. Transcriptional expression levels of selected myelin- or oligodendroglia-related genes implicated in schizophrenia or ASD development were analyzed by in situ hybridization (ISH) and quantitative real-time PCR (qRT-PCR) with brain samples from MIA and control groups. The analysis focused on SOX-10 (SRY-related HMG-box 10), MAG (myelin associated glycoprotein) and Tf (transferrin) expression in the hippocampus and the surrounding memory-related cortical regions in either hemisphere. Results: Specifically, ISH reveals that, in the brain of prenatal poly(I:C)-exposed mouse offspring (gestation day 9), mRNA expression of the genes SOX10, MAG and Tf was generally reduced in the limbic system including the hippocampus, retrosplenial cortex and parahippocampal gyrus on either side of the hemispheres. qRT-PCR further confirms the reduction of SOX10, MAG and Tf expression in the medial prefrontal cortex, sensory cortex, amygdala and hippocampus. Conclusions: Our present results provide direct evidence that prenatal exposure to poly(I:C) elicits profound and long-term changes in transcript level and spatial distribution of myelin-related genes in multiple neocortical and limbic regions, notably the hippocampus and its surrounding memory-related neural networks. Our work demonstrates the potential utility of oligodendroglia-related genes as biomarkers for modeling neurodevelopmental disorders and supports the hypothesis that MIA during pregnancy could lead to compromised white matter connectivity in ASD.